Development of wound SiCBNx/SiNx/SiC with near stoichiometric SiC matrix via LSI process. Issue 7 (June 2016) - Mainzer, Bernd; Roder, Kristina; Wöckel, Lydia; Frieß, Martin; Koch, Dietmar; Nestler, Daisy; Wett, Daniel; Podlesak, Harry; Wagner, Guntram; Ebert, Thomas; Spange, Stefan
Abstract: In order to develop SiC/SiC ceramic matrix composites with a low porosity, liquid silicon infiltration (LSI) was chosen as a technique, characterized by short processing times. To create the matrix, a tailored phenolic resin containing ß-naphthol units was synthesized and infiltrated in wound fiber preforms, thermally cured, pyrolysed and siliconized. The aim is to obtain a high carbon yield during pyrolysis and to create a dense carbon foam between the SiC fibers. Instead of a classic liquid silicon infiltration via capillary forces through a carbon block-like microstructure, this foam promotes a softer infiltration with less fiber degradation and a maximized carbon conversion to near stoichiometric SiC. To protect the SiC fibers from an attack of the liquid silicon and to simultaneously provide a weak fiber matrix bonding, a BNx /SiNx fiber coating was chosen. The coating was applied by means of low-pressure chemical vapor deposition (LPCVD) using gaseous chlorine free precursors.